2014
DOI: 10.1091/mbc.e13-11-0658
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor protein GULP promotes Jedi-1–mediated phagocytosis through a clathrin-dependent mechanism

Abstract: The engulfment receptor Jedi-1 mediates phagocytosis through association with the adaptor GULP, which results in the recruitment and tyrosine phosphorylation of clathrin heavy chain. Preventing GULP association with clathrin or its phosphorylation inhibits Jedi-mediated engulfment, indicating a noncanonical role for clathrin in phagocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Therefore, we asked whether megf6 takes on this role in planarians, which lack a MEGF10/11 ortholog. Interestingly, planarians do have orthologs of many of the regulators of phagocytosis downstream of Draper/Ced-1/MEGF10/11 in flies and C. elegans, including ABCA1, shark, ELMO, and gulp [36][37][38][39]. However, upon RNAi knockdown we found that none of these genes reproduced the knockdown phenotypes of megf6 (S3 Fig).…”
Section: Megf6 Is An Uncharacterized Gene Conserved In Metazoansmentioning
confidence: 91%
“…Therefore, we asked whether megf6 takes on this role in planarians, which lack a MEGF10/11 ortholog. Interestingly, planarians do have orthologs of many of the regulators of phagocytosis downstream of Draper/Ced-1/MEGF10/11 in flies and C. elegans, including ABCA1, shark, ELMO, and gulp [36][37][38][39]. However, upon RNAi knockdown we found that none of these genes reproduced the knockdown phenotypes of megf6 (S3 Fig).…”
Section: Megf6 Is An Uncharacterized Gene Conserved In Metazoansmentioning
confidence: 91%
“…The protein markers chosen for analysis here have been used to identify a variety of cells with phagocytic activity, including cells of the monocyte-macrophage lineage [1922]. To our knowledge their expression has not been described in mesenchymal progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) severity was defined in accordance with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification: based on post-bronchodilator forced expiratory volume in 1 s (FEV 1 ) in patients with FEV 1 /forced vital capacity (FVC) < 0.7, GOLGD I (mild) is FEV 1 80% predicted, GOLD II (moderate) is 50% FEV 1 < 80% predicted, GOLD III (severe) is 30% FEV 1 < 50% predicted, and GOLD IV (very severe) is FEV 1 < 30% predicted. considered to have a functional role in the phagocytic process, where it was identified in a screen for genes regulating the clearance of apoptotic cells [15,16,35,36]. GULP1, an apoptosisassociated gene was suggested to play a role in the pathogenesis of some human disease such as arthritis and schizophrenia [17,18].…”
Section: Variablesmentioning
confidence: 99%